Work Activity Challenges among Hemodialysis Patients and Their Impact on Quality of Life - Nicole Caldeira Skrebsky Menegazzo; Israel Kitzberger; Mateus de Miranda Gauza; Claudia Sombrio Fronza; Antonio Vinicius Soares; Helbert do Nascimento Lima (O Mundo da Saúde, 2023)
Most patients undergoing hemodialysis are of working age, and this poses a challenge in maintaining their jobs. A crosssectional study was carried out in hemodialysis centers in the north of Santa Catarina, between December 2020 and February 2021. Patients aged between 18 and 55 years old on hemodialysis for more than 3 months were included. Aspects related to work, remaining at their job after starting hemodialysis, and quality of life were evaluated using the SF-36 instrument. Their working situation was evaluated in relation to quality of life through logistic regression. Of the 108 patients, the mean age was 43.34 ± 8.88 years old, with a median time on dialysis of 19 months. Of the participants, 78.9% were working six months before starting hemodialysis and 39.8% were working 6 months after. There was no difference in terms of sex, age, and marital status with regards to work before or after 6 months of starting hemodialysis. Working was associated with a better quality of life, even after adjusting for other variables (OR=5.30; 95% CI 1.43-19.61, p=0.013). It is concluded that there is a significant drop in employment after starting hemodialysis. The stimulus to keep working can favor a better quality of life in these patients.